ISOLASI DAN IDENTIFIKASI SENYAWA SAPONIN EKSTRAK BUTANOL DAUN MAJAPAHIT (Cresentia cujete) DENGAN METODE ROMATOGRAFI LAPIS TIPIS DAN SPEKTROFOTOMETRI INFRA MERAH - Firawati Firawati (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2018)
Isolation and identification saponin compound had been done butanol extract of Majapahit leaf (Cresentia cujete), The results showed that pure isolate by butanol extract Majapahit leaf in Rf value of 0.6 allegedly identified the saponin compounds at foam test and infra red spectrum results of which is marked by the presence of O-H,  C=C, C-C, and C-H groups. Keywords : Saponin, Majapahit (Cresentia cujete), TLC, and spectrophotometry infra red.